Positive electrode active material and preparation method thereof, positive electrode plate, battery and application

By using dodecimal phosphotungstic acid modification and conductor layer coating technology in the positive electrode material of lithium iron phosphate battery, the problem of reduced cycle stability when the existing materials are improved is solved, and efficient charging and discharging performance and structural protection are achieved .

CN119315007APending Publication Date: 2025-01-14HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411435221.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

When the existing lithium iron phosphate battery positive electrode materials improve rate performance, their cycle stability and service life will be reduced, and the ion diffusion rate cannot be effectively improved through surface carbon coating alone.

Method used

The lithium iron phosphate core modified by dodecytungstic acid, plus an ionic conductor layer and conductive carbon layer are prepared through acidification-hydrothermal reaction and spray granulation technology to form a positive electrode active material with high symmetry and stability.

Benefits of technology

The cycle stability and rate performance of the positive electrode active material are significantly improved, ensuring good charge and discharge performance and structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315007A_ABST
    Figure CN119315007A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a positive active material, a preparation method thereof, a positive pole piece, a battery and application. The positive electrode active material comprises a lithium iron phosphate core modified by dodecaphosphotungstic acid; and an ion conductor layer and a conductive carbon layer are sequentially arranged outside the inner core. The ionic conductivity of the positive electrode active material is effectively improved by the ionic conductor layer; the conductive carbon layer not only improves the conductivity of the positive electrode active material, but also can protect the material wrapped in the positive electrode active material, so that the structure of the material is not easily damaged. The positive electrode active material provided by the invention has good charge-discharge performance and very high cycling stability and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery, and applications. Background Art

[0002] The commonly used lithium battery positive electrode material lithium iron phosphate (LiFePO4) has the characteristics of high thermal stability and long cycle life, but low rate performance. The common way to improve its rate performance is to dope it with metals (such as manganese, cobalt, nickel, aluminum, titanium, etc.) or non-metals (such as nitrogen, sulfur, fluorine, etc.). Although it can effectively improve the conductivity and ion diffusion coefficient of lithium iron phosphate, thereby improving its rate performance, its cycle stability and service life will be reduced due to the doping of elements. In addition, doping elements also have limited effect on improving rate performance.

[0003] At present, coating lithium iron phosphate materials with carbon materials can significantly improve the electronic conductivity of the materials. However, if only the carbon coating is performed on the surface of the material, although the conductivity can be improved, the problem of slow ion diffusion rate still exists, which makes it difficult for the modified positive electrode active material to achieve the expected effect. Summary of the invention

[0004] In order to solve the above problems, the present application proposes a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery, and an application thereof. The positive electrode active material has good charge and discharge performance, high cycle stability and rate performance.

[0005] This application is implemented through the following technical solutions:

[0006] In a first aspect, the present application provides a positive electrode active material, the positive electrode active material comprising a lithium iron phosphate core modified with dodecaphosphotungstic acid; the core is provided with an ion conductor layer and a conductive carbon layer in order from the outside;

[0007] The molar ratio of the lithium iron phosphate to the dodecaphosphotungstic acid is 12:0.01-0.02.

[0008] In the positive electrode active material of the present application, the dodecaphosphotungstic acid has a cage structure with high symmetry and stability. In the lithium iron phosphate modified by dodecaphosphotungstic acid, the lithium ions are located in the gap of the crystal structure formed by the olivine structure of the lithium iron phosphate modified by the cage structure, which is easy to embed and remove, effectively improving the cycle stability and rate performance of the positive electrode active material; the ion conductor layer effectively improves the ion conductivity of the positive electrode active material; the conductive carbon layer not only improves the conductivity of the positive electrode active material, but also protects the material coated therein, so that the structure of the material is not easily destroyed. The positive electrode active material described in the present application has good charge and discharge performance, high cycle stability and rate performance.

[0009] In some possible implementations, the ion conductor layer is at least one layer, and the thickness of the single ion conductor layer is 2 nm to 30 nm.

[0010] In some possible implementations, the conductive carbon layer is at least one layer, and the thickness of the single conductive carbon layer is 5 nm to 20 nm.

[0011] In some possible implementations, the tap density of the positive electrode active material is 0.8 g / cm 3 ~1.35 / cm 3 .

[0012] In a second aspect, the present application proposes a method for preparing the positive electrode active material proposed in the present application, comprising the following steps:

[0013] The suspension is subjected to an acidification-hydrothermal reaction to obtain a lithium iron phosphate matrix modified with dodecaphosphotungstic acid; wherein the suspension comprises components of lithium iron phosphate, sodium tungstate and disodium hydrogen phosphate;

[0014] The lithium iron phosphate matrix modified with dodecaphosphotungstic acid is dried and washed, and then spray granulated, ion conductor coated and carbon coated to obtain a positive electrode active material.

[0015] The preparation method of the positive electrode active material of the present application comprises the following steps: in the acidification-hydrothermal reaction, disodium hydrogen phosphate and phosphoric acid are used to in-situ synthesize dodecaphosphotungstic acid and simultaneously modify lithium iron phosphate to obtain the matrix; after spray granulation, an ion conductor layer and a conductive carbon layer are coated to obtain the positive electrode active material; the positive electrode active material has good charge and discharge performance, high cycle stability and rate performance.

[0016] In some possible implementations, the acidification-hydrothermal reaction comprises the steps of:

[0017] Adjusting the pH value of the suspension to 6-7;

[0018] The matrix is ​​obtained by performing a hydrothermal reaction at 120° C. to 135° C. for 10 h to 12 h.

[0019] In some possible implementations, the molar ratio of the lithium iron phosphate, the sodium tungstate and the disodium hydrogen phosphate is 12:(0.12-0.2):(0.01-0.017).

[0020] In some possible implementations, the spray drying includes pressure spray drying, in which the air inlet temperature is 200° C. to 300° C., the air outlet temperature is 95° C. to 100° C., and the air inlet pressure is 0.2 MPa to 0.6 MPa.

[0021] In a third aspect, the present application proposes a positive electrode plate, wherein the positive electrode plate includes the positive electrode active material described in the present application or the positive electrode active material prepared by the preparation method described in the present application.

[0022] In a fourth aspect, the present application provides a battery, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte;

[0023] The positive electrode plate includes the positive electrode plate described in the present application.

[0024] In the fifth aspect, the present application proposes an application of the positive electrode active material proposed in the present application, the positive electrode active material prepared by the preparation method of the positive electrode active material proposed in the present application, the positive electrode plate proposed in the present application, or the battery proposed in the present application in household appliances, electric vehicles, electric cars, electric trains, ships, satellites or energy storage systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0026] Figure 1 A schematic diagram of a process for preparing a positive electrode active material in an embodiment of the present application;

[0027] Figure 2 This is a SEM image of the positive electrode active material in Example 1 of the present application.

[0028] The purpose, features and advantages of this figure will be further described in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION

[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0030] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0031] In the present application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.

[0032] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX can also be called the second XX, and similarly, the second XX can also be called the first XX. Therefore, the features defined as "first" and "second" can explicitly or implicitly include one or more of the features.

[0033] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0034] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.

[0035] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0038]

Positive electrode active material

[0039] In a first aspect, an embodiment of the present application provides a positive electrode active material, which includes a lithium iron phosphate core modified with dodecaphosphotungstic acid; an ion conductor layer and a conductive carbon layer are arranged in sequence from the core to the outside.

[0040] In the positive electrode active material of the embodiment of the present application, dodecaphosphotungstic acid has a cage structure with high symmetry and stability. In the lithium iron phosphate modified by dodecaphosphotungstic acid, lithium ions are located in the gap of the crystal structure formed by the olivine structure of lithium iron phosphate modified by the cage structure, which is easy to embed and remove, effectively improving the cycle stability and rate performance of the positive electrode active material; the ion conductor layer effectively improves the ion conductivity of the positive electrode active material; the conductive carbon layer not only improves the conductivity of the positive electrode active material, but also protects the material coated therein, so that the structure of the material is not easily destroyed. The positive electrode active material of the embodiment of the present application has good charge and discharge performance, high cycle stability and rate performance.

[0041] In some embodiments, the molar ratio of lithium iron phosphate to dodecaphosphotungstic acid is 12:0.01-0.02. In the exemplary embodiment, it can be a typical but non-limiting molar ratio such as 12:0.01, 12:0.015, 12:0.02, or a range between any two molar ratios. In this case, lithium iron phosphate modified with dodecaphosphotungstic acid can effectively improve the cycle stability and rate performance of the positive electrode active material.

[0042] In some embodiments, the ion conductor layer is at least one layer, and the thickness of the single ion conductor layer is 2 nm to 30 nm. In the exemplary embodiment, the thickness can be 2 nm, 5 nm, 10 nm, 20 nm, 30 nm, etc., which are typical but not limiting, or a range between any two thicknesses. In this case, the ion conductor layer effectively improves the ionic conductivity of the positive electrode active material.

[0043] In some embodiments, the material of the ion conductor layer is an inorganic conductor material or an organic conductor material.

[0044] In some embodiments, the inorganic lithium conductor material includes LiAlF4, Li 1+x Al x Ti 2-x In this case, the inorganic lithium conductor material can optimize the ion transmission path of lithium iron phosphate and significantly improve the electrochemical performance of lithium iron phosphate (such as capacity, cycle life and safety, etc.).

[0045] In some embodiments, the organic lithium conductor material includes at least one of polyimide and polyvinylidene fluoride-trifluoroethylene copolymer. In this case, the organic conductor material has good ionic conductivity and mechanical stability, and improves the electrochemical performance of lithium iron phosphate.

[0046] In some embodiments, the conductive carbon layer is at least one layer, and the thickness of the single conductive carbon layer is 5nm to 20nm. In the exemplary embodiment, the thickness can be 5nm, 10nm, 20nm, etc., which are typical but non-limiting thicknesses, or a range between any two thicknesses.

[0047] In some embodiments, the tap density of the positive electrode active material is 0.8 g / cm 3 ~1.35g / cm 3 In the example, it can be 0.85g / cm 3 , 0.95g / cm 3 , 1.15g / cm 3 , 1.25g / cm 3 , 1.35g / cm 3 Typical but non-limiting tap densities or a range between any two tap densities. Within this tap density range, the energy density of the positive electrode active material is effectively increased.

[0048] [A method for preparing a positive electrode active material]

[0049] In a second aspect of the present application, a method for preparing a positive electrode active material is provided. Figure 1 As shown, the following steps are included:

[0050] S10. The suspension is subjected to an acidification-hydrothermal reaction to obtain a lithium iron phosphate matrix modified with dodecaphosphotungstic acid; wherein the suspension includes components of lithium iron phosphate, sodium tungstate and disodium hydrogen phosphate.

[0051] S20. Dry and wash the lithium iron phosphate matrix modified with dodecaphosphotungstic acid, and then spray granulate, ion conductor coat and carbon coat to obtain a positive electrode active material.

[0052] The preparation method of the positive electrode active material of the embodiment of the present application is as follows: in an acidification-hydrothermal reaction, disodium hydrogen phosphate and phosphoric acid are used to in situ synthesize dodecaphosphotungstic acid and simultaneously modify lithium iron phosphate to obtain a matrix; after spray granulation, an ion conductor layer and a conductive carbon layer are coated to obtain a positive electrode active material; the positive electrode active material has good charge and discharge performance, high cycle stability and rate performance.

[0053] [Step S10]

[0054] In some embodiments, in the above step S10, the preparation of the suspension includes the steps of: mixing sodium tungstate, disodium hydrogen phosphate and water in a preset ratio to obtain a mixed solution, and then dispersing lithium iron phosphate in the mixed solution under stirring conditions to obtain a suspension.

[0055] In some specific embodiments, the molar ratio of lithium iron phosphate, sodium tungstate and disodium hydrogen phosphate is 12:(0.12-0.2):(0.01-0.017), and in the exemplary embodiment, it can be a typical but non-limiting molar ratio such as 12:0.12:0.01, 12:0.2:0.017, or a range between any two molar ratios. In this case, sodium tungstate is completely reacted in situ to generate dodecaphosphotungstic acid and simultaneously modify lithium iron phosphate.

[0056] In some embodiments, in the above step S10, the suspension further includes a surfactant. The surfactant can promote the uniform dispersion of lithium iron phosphate in the suspension. The material of the surfactant can be any material that meets the requirements, and is not mandatory, but as an example, the surfactant can be sodium dodecylbenzene sulfonate (SDBS), hexadecyltrimethylammonium bromide (CTAB), etc.

[0057] In some embodiments, the mass of the surfactant is 0.1% to 1% of the mass of the lithium iron phosphate. In exemplary embodiments, it can be 0.1%, 0.5%, 1%, or other typical but non-limiting mass percentages or a range between any two mass percentages.

[0058] In some embodiments, the mass fraction of sodium tungstate in the mixed solution is 10% to 26.2%. In the exemplary embodiment, it can be 10%, 15%, 26.2% or other typical but non-limiting mass fractions or a range between any two mass fractions.

[0059] In some embodiments, the mass fraction of disodium hydrogen phosphate in the mixed solution is 0.2% to 1.7%. In exemplary embodiments, it can be 0.2%, 0.8%, 1.0%, 1.7%, or other typical but non-limiting mass fractions or a range between any two mass fractions.

[0060] In some embodiments, in the above step S10, the acidification-hydrothermal reaction comprises the steps of:

[0061] S11. Adjust the pH value of the suspension to 6-7.

[0062] S12. Carry out a hydrothermal reaction at 120°C to 135°C for 10 h to 12 h to obtain a matrix.

[0063] In the above-mentioned mixing reaction step, the pH value of the suspension is adjusted to make the suspension acidic, sodium tungstate and disodium hydrogen phosphate react preliminarily to generate dodecaphosphotungstic acid, and then a hydrothermal reaction is performed to stabilize the generated dodecaphosphotungstic acid and modify the lithium iron phosphate.

[0064] In some specific embodiments, in the above step S11, the step of adjusting the pH value of the suspension includes: adjusting the pH value of the suspension with a pH adjuster under stirring conditions. The stirring speed is 100 rpm to 200 rpm. In the exemplary embodiment, it can be a typical but non-limiting stirring speed such as 100 rpm, 150 rpm, 200 rpm, or a range between any two stirring speeds; the speed of adding the pH adjuster is 10 d / min to 30 d / min. In the exemplary embodiment, it can be a typical but non-limiting speed such as 10 d / min, 15 d / min, 20 d / min, 25 d / min, 30 d / min, or a range between any two speeds. In this speed range, combined with the stirring speed, precipitation caused by excessive local concentration can be avoided.

[0065] In some specific embodiments, the stirring time is 30 min to 3 h, and in exemplary examples, it can be 30 min, 1 h, 2 h, 3 h, etc., typical but non-limiting time or a range between any two time periods. In this case, phosphoric acid and ammonium molybdate can fully react to form ammonium phosphomolybdate.

[0066] In some specific embodiments, the pH adjuster is hydrochloric acid, nitric acid or phosphoric acid. In this case, hydrochloric acid or nitric acid are both strong acids, and adding a small amount of hydrochloric acid or nitric acid can adjust the pH value to 6-7 to avoid introducing too many impurities; while phosphoric acid can avoid introducing other impurities. In addition, hydrochloric acid and nitric acid are easy to remove.

[0067] In some specific embodiments, the concentration of nitric acid is 3% to 30%. In exemplary embodiments, it can be 3%, 8%, 10%, 20%, 30% or other typical but non-limiting mass fractions or a range between any two mass fractions.

[0068] In some specific embodiments, the mass concentration of dilute nitric acid is 3% to 30%. In the exemplary examples, it can be 3%, 8%, 10%, 20%, 30% or other typical but non-limiting mass fractions or a range between any two mass fractions.

[0069] In some embodiments, the mass concentration of phosphoric acid is 60% to 85%. In exemplary embodiments, it can be 60%, 70%, 80%, 85%, or other typical but non-limiting mass concentrations or a range between any two mass concentrations.

[0070] [Step S20]

[0071] In some embodiments, in the above step S20, the drying temperature is 100°C to 150°C, and the drying time is 0.5h to 3h; in an exemplary embodiment, the drying temperature can be 100°C, 120°C, 140°C, 150°C, etc., typical but non-limiting temperatures or a range between any two temperatures, and the drying time can be 0.5h, 2h, 3h, etc., typical but non-limiting times or a range between any two times. At this drying temperature and time, the solvent in the precursor is removed.

[0072] In some embodiments, in the above step S20, the dried product is washed multiple times with a small amount of dilute hydrochloric acid or dilute phosphoric acid, the washing times are at least 3 times, and the volume of dilute hydrochloric acid or dilute phosphoric acid for a single washing is less than 0.2 times the volume of the substrate. In this case, acid washing can prevent the generated dodecaphosphotungstic acid from dissolving again.

[0073] In some embodiments, in the above step S20, spray drying includes pressure spray drying.

[0074] In some embodiments, the air inlet temperature in the pressure spray drying is 200°C to 300°C, the air outlet temperature is 95°C to 100°C, and the air inlet pressure is 0.2MPa to 0.6MPa. In the exemplary embodiment, the air inlet temperature of the spray drying can be a typical but non-limiting temperature such as 200°C, 250°C, 300°C, or a range between any two temperatures, and the air inlet pressure can be a typical but non-limiting time such as 0.2MPa, 0.4MPa, 0.6MPa, or a range between any two pressures. Under this spray granulation temperature and pressure, not only the Keggin structure of the dodecaphosphotungstic acid in the prepared positive electrode active material will not be destroyed, but also the contact interface between lithium iron phosphate and dodecaphosphotungstic acid can be stabilized, thereby improving the conductivity and conductivity rate of the positive electrode active material; in addition, the stable contact interface further stabilizes the Keggin structure, so that the lithium iron phosphate modified with dodecaphosphotungstic acid will not be destroyed in the high temperature environment in the subsequent ion conductor coating and carbon coating steps.

[0075] In some specific embodiments, the high pressure gas in the spray drying is compressed air or an inert gas. In this case, the air or the inert gas does not chemically react with the material, and therefore does not generate new impurities.

[0076] In some specific embodiments, the inert gas is at least one of nitrogen, helium, neon, and argon.

[0077] In some specific embodiments, in the above step S20, the average particle size Dv50 of the product obtained by spray drying is 1 μm to 15 μm, and in the exemplary embodiment, it can be a typical but non-limiting average particle size such as 1 μm, 2 μm, 6 μm, 8 μm, 15 μm, or a range between any two average particle sizes. In this case, the particle size range can make the particle surface uniformly coated with the ion conductor layer and the conductive carbon layer, thereby improving the conductivity of the positive electrode active material.

[0078] In some embodiments, in the above step S20, the ion conductor coating step includes:

[0079] The ion conductor coating source compound, the chelating agent and the solvent are mixed to form a colloidal solution; then the lithium iron phosphate modified with dodecaphosphotungstic acid is mixed with the colloidal solution to carry out a solvothermal reaction to obtain the lithium iron phosphate modified with dodecaphosphotungstic acid coated with the ion conductor.

[0080] In some embodiments, the ion conductor coating source compound is related to the material of the final desired ion conductor layer. As an example, when the ion conductor layer is LiAlF4, the ion conductor coating source compound is a lithium source (such as lithium carbonate), an aluminum source (such as trimethylaluminum, AlCl3) and a fluorine source (such as hydrogen fluoride solution, hydrogen fluoride pyrrole solution).

[0081] In some embodiments, the chelating agent includes at least one of gluconolactone, citric acid, and acetic acid. In this case, these chelating agents can form stable complexes with metal ions and decompose or convert into harmless substances in the subsequent reaction process.

[0082] In some embodiments, the solvent is a mixture of alcohol and water in a mass ratio of (5 to 10): 1, and the alcohol includes at least one of methanol, ethanol, ethylene glycol, and glycerol. In this case, the solvent can dissolve the ion conductor coating source compound and the chelating agent, and coordinate to form a stable complex colloidal solution, and will not cause the dissolution of the dodecaphosphotungstic acid when subsequently mixed with the lithium iron phosphate modified with dodecaphosphotungstic acid.

[0083] In some embodiments, the solvothermal reaction is carried out in an inert atmosphere at a temperature of 150°C to 300°C.

[0084] In some embodiments, in the above step S20, the lithium iron phosphate modified with dodecaphosphotungstic acid containing an ion conductor layer is carbon-coated by chemical vapor deposition. It should be noted that the coating conditions such as the gas and temperature of the chemical vapor deposition method can be adjusted according to actual conditions and are not limited. In the embodiment, the deposition temperature of the chemical vapor deposition method is 600°C to 1000°C, which can be a typical but non-restrictive temperature such as 600°C, 650°C, 800°C, 850°C, 900°C, 1000°C, or a range between any two temperatures. In the embodiment, the carbon source of the chemical vapor deposition method includes but is not limited to one or more of methane, ethane, ethylene, and acetylene.

[0085] In other embodiments, in the above step S20, the lithium iron phosphate modified with dodecaphosphotungstic acid containing an ion conductor layer is carbon-coated by a sintering method. It should be noted that the coating conditions of the sintering method can also be adjusted according to actual conditions and are not limited. As an example, the steps of carbon coating by the sintering method include: glucose and the modified lithium iron phosphate are mixed in a certain mass ratio (between 1.5% and 3%), pure water is used as a dispersant, the solid content is controlled at 33%-40%, the sand mill is stirred for 40 minutes, and the dried material is spray-dried after being taken out, and the dried material is placed in a kiln for sintering, and an inert gas such as argon is used as a protective gas. The heating rate is controlled at 5-10min / ℃, the constant temperature section is controlled at 750-810℃, the insulation period is 15-19h, and it is cooled naturally.

[0086]

Positive electrode

[0087] A third aspect of the embodiments of the present application provides a positive electrode plate, which includes the positive electrode active material of the embodiments of the present application or the positive electrode active material prepared by the preparation method of the embodiments of the present application.

[0088] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode film layer disposed on at least one surface of the current collector;

[0089] The positive electrode film layer contains the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application.

[0090] In the above-mentioned “at least one surface of the current collector”, the surface refers to the surface of the current collector perpendicular to the thickness direction of the current collector.

[0091] Exemplarily, the thickness of the positive electrode plate is 0.15 mm to 10 mm; this thickness is only exemplary, and the thickness can be adjusted according to actual needs and is not limited to this thickness range.

[0092] In some embodiments, the current collector material includes one or more of a carbon material, a metal material, and a carbon fiber composite material.

[0093] In some embodiments, the carbon material includes one or more of natural graphite, artificial graphite, carbon black, and carbon fiber.

[0094] In some embodiments, the metal material includes one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, copper, and copper alloy.

[0095] In some embodiments, the positive electrode film layer contains the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application.

[0096] In some embodiments, the method for preparing a positive electrode film generally includes:

[0097] The positive electrode slurry containing the positive electrode active material is coated on the current collector, and the positive electrode film layer is obtained through the steps of drying and cold pressing.

[0098] Exemplarily, the thickness of the positive electrode film layer is 0.1 mm to 8 mm; this thickness is only exemplary, and the thickness can be adjusted according to actual needs and is not limited to this thickness range.

[0099]

Battery

[0100] A fourth aspect of the present application provides a battery, including a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte;

[0101] The positive electrode plate includes the positive electrode plate of the embodiment of the present application.

[0102] The battery of the embodiment of the present application has excellent conductivity, cycle stability and rate performance because the positive electrode uses a positive electrode plate containing the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application, thereby making the positive electrode of the battery have excellent conductivity, cycle stability and rate performance.

[0103] In some embodiments, the isolation membrane includes one or more of a porous polymer membrane, a non-woven fabric membrane, and an inorganic composite membrane.

[0104] In some embodiments, the material of the porous polymer membrane includes polyethylene (PE) and / or polypropylene (PP).

[0105] In some embodiments, the material of the non-woven fabric separator includes one or more of polyimide (PI), polyester (such as polyethylene terephthalate PET), cellulose, polyamide (PA), and aramid.

[0106] In some embodiments, the nonwoven membrane is a nanofiber nonwoven membrane, including a polyimide nanofiber membrane. In this case, the nanofiber nonwoven membrane has a higher specific surface area and stronger adsorption capacity, and can more effectively isolate the positive and negative electrodes and promote the transmission of lithium ions.

[0107] In some embodiments, the non-woven membrane is a ceramic-coated non-woven membrane, that is, a ceramic powder (such as Al2O3, SiO2, etc.) is coated on the surface of the non-woven membrane (thickness 2μm to 15μm). This ceramic-coated non-woven membrane not only inherits the high porosity and air permeability of the non-woven fabric, but also increases its thermal stability and mechanical strength.

[0108] In some embodiments, the inorganic composite membrane includes a ceramic-coated composite membrane and an inorganic-organic composite membrane;

[0109] Among them, the ceramic-coated composite membrane is a polymer membrane (such as polyethylene PE, polypropylene PP, etc.) coated with one or more layers of ceramic coating; the ceramic coating can significantly improve the thermal stability and chemical stability of the membrane while maintaining the flexibility and mechanical strength of the polymer membrane;

[0110] Inorganic-organic composite membranes are made by combining inorganic materials with polymer materials through blending, copolymerization or lamination. This composite membrane combines the advantages of inorganic materials and polymer materials and has higher comprehensive performance.

[0111] In some embodiments, the isolation film has a thickness of 60 μm to 100 μm.

[0112] In some embodiments, the negative electrode plate is a common battery plate, generally including a current collector and a negative electrode film layer; the negative electrode film layer contains a negative electrode active material, and the specific negative electrode material and content can be selected according to actual needs without limitation. The preparation of the negative electrode film layer is basically the same as that of the positive electrode film layer.

[0113] In some embodiments, the electrolyte includes an electrolyte salt and a solvent. The materials and contents of the electrolyte salt and the solvent are selected according to actual needs and are not limited.

[0114] The following describes the invention in conjunction with specific embodiments.

[0115] Example 1

[0116] Example 1 provides a method for preparing a positive electrode active material, comprising the following steps:

[0117] (1) With the molar ratio of lithium iron phosphate, sodium tungstate and disodium hydrogen phosphate being 12:0.12:0.01 and water being used as solvent, sodium tungstate, disodium hydrogen phosphate and water are first mixed to obtain a mixed solution, and then lithium iron phosphate is dispersed in the mixed solution under stirring conditions to obtain a suspension.

[0118] (2) Use hydrochloric acid to adjust the pH value of the suspension to 6-7.

[0119] (3) A hydrothermal reaction was carried out at 130° C. for 11 h to obtain a lithium iron phosphate matrix modified with dodecaphosphotungstic acid.

[0120] (4) The substrate was dried at 120° C. for 2 h; after washing four times with a single wash volume of dilute hydrochloric acid of 0.2 times the volume of the substrate, spray granulation was performed under hot air at 350° C. for 5 min.

[0121] (5) Lithium carbonate, AlCl3, hydrogen fluoride pyrrole solution, gluconolactone and a solvent are mixed to form a colloidal solution, wherein the solvent is a mixture of alcohol and water in a mass ratio of 8:1.

[0122] (6) In a helium atmosphere at 200° C., the lithium iron phosphate modified with dodecaphosphotungstic acid is mixed with a colloidal solution to undergo a solvothermal reaction to obtain the lithium iron phosphate modified with dodecaphosphotungstic acid coated with an ion conductor.

[0123] (7) Using acetylene as a carbon source, a conductive carbon layer with a thickness of 15 nm is coated on the surface of lithium iron phosphate modified with dodecaphosphotungstic acid coated with an ion conductor by chemical vapor deposition, wherein the deposition temperature is 650°C.

[0124] Example 1 also provides a positive electrode active material, which is prepared using the preparation method of this example.

[0125] The tap density of the positive electrode active material is 1.35 g / cm 3 .

[0126] Example 2

[0127] Example 2 proposes a positive electrode active material and a preparation method thereof. The material and the preparation steps thereof are substantially the same as those of Example 1, except that in the preparation method, the molar ratio of lithium iron phosphate, sodium tungstate and disodium hydrogen phosphate is 12:0.2:0.017.

[0128] The tap density of the positive electrode active material is 1.24 g / cm 3 .

[0129] Example 3

[0130] Example 3 proposes a positive electrode active material and a preparation method thereof. The material and the preparation steps are basically the same as those in Example 1, except that: in the preparation method, in step (7), the ion conductor-coated dodecaphosphotungstic acid-modified lithium iron phosphate is carbon-coated by a sintering method. The specific coating method is: using glucose as a carbon source, the mass of glucose is 2% of the mass of the ammonium phosphomolybdate-modified lithium iron phosphate coated with gallium nitride; mixing glucose, the ion conductor-coated dodecaphosphotungstic acid-modified lithium iron phosphate and water and sintering them. The sintering environmental conditions are: using argon or other inert gas as a protective gas, the heating rate is 8°C / min, the constant temperature section is controlled at 790°C, the insulation period is 17h, and natural cooling is performed to obtain a conductive carbon layer with a thickness of 10nm.

[0131] The tap density of the positive electrode active material is 1.15 g / cm 3 .

[0132] Comparative Example 1

[0133] Comparative Example 1 proposes a method for preparing a positive electrode active material, and the steps are basically the same as those of Example 1, except that the pH value of the precursor is 9.

[0134] Comparative Example 1 also provides a positive electrode active material, which is prepared using the preparation method of this comparative example.

[0135] The tap density of the positive electrode active material is 1.05 g / cm 3 .

[0136] Comparative Example 2

[0137] Comparative Example 2 proposes a method for preparing a positive electrode active material, and the steps are basically the same as those of Example 1, except that in the preparation method, the molar ratio of lithium iron phosphate, sodium tungstate and disodium hydrogen phosphate is 12:0.12:0.005.

[0138] Comparative Example 3 also proposes a positive electrode active material, which is prepared by the preparation method of this comparative example. The tap density of the positive electrode active material is 0.89 g / cm 3 .

[0139] Comparative Example 3

[0140] Comparative Example 3 proposes a method for preparing a positive electrode active material, and the steps are basically the same as those of Example 1, except that the preparation method does not coat the ion conductor, that is, step (5) and step (6) are not performed.

[0141] Comparative Example 3 also proposes a positive electrode active material, which is prepared using the preparation method of this comparative example.

[0142] The tap density of the positive electrode active material is 0.99 g / cm 3 .

[0143] Comparative Example 4

[0144] Comparative Example 4 proposes a method for preparing a positive electrode active material, and the steps are basically the same as those of Example 1, except that: the preparation method does not coat the conductive carbon layer, that is, step (7) is not performed.

[0145] Comparative Example 4 also proposes a positive electrode active material, which is prepared using the preparation method of this comparative example.

[0146] The tap density of the positive electrode active material is 0.91 g / cm 3 .

[0147] In order to verify the advancement of the positive electrode active material and the preparation method thereof proposed in the examples of the present application, firstly, taking Example 1 as an example, a scanning electron microscope was used to scan the positive electrode active material prepared in Example 1, and the corresponding Figure 2 The SEM image shown; the positive electrode active materials prepared in the embodiment and the comparative example are then made into button batteries, and the preparation steps are as follows:

[0148] (1) Preparing positive electrode slurry: positive electrode active material: carbon nanotube: polyvinylidene fluoride were mixed in a mass ratio of 90:5:5, and solvent N-methylpyrrolidone (NMP) was added to adjust the viscosity to 4000 mPa·s to 8000 mPa·s to prepare positive electrode slurry.

[0149] (2) The positive electrode slurry is evenly coated on one surface (perpendicular to the thickness direction) of the aluminum foil (positive electrode current collector) and dried, and then rolled and sliced ​​to obtain a positive electrode sheet containing a positive electrode film layer.

[0150] (5) Using lithium hexafluorophosphate-ethyl methyl carbonate as the electrolyte and polypropylene as the isolation membrane, the prepared positive electrode sheet and negative lithium sheet are combined to form a button half-cell.

[0151] The button cell was tested for electrical properties in the voltage range of 2.0V to 3.8V using a Blue Electric device, including 0.1C discharge, 0.1C first charge and discharge efficiency, 5C discharge, and 1C cycle 500 times capacity retention rate. The test results are shown in Table 1 below.

[0152] Table 1

[0153]

[0154] From the above table 1 and Figure 2 At least the following conclusions can be drawn:

[0155] 1) It can be obtained from Example 1 and Comparative Examples 3 and 4 that in the positive electrode active material provided in the embodiments of the present application, the positive electrode active material of lithium iron phosphate modified with dodecaphosphotungstic acid double-layered with an ion conductor layer and a conductive carbon layer has good charge and discharge performance, high cycle stability and rate performance.

[0156] 2) It can be seen from Example 1 and Comparative Example 1 that dodecaphosphotungstic acid-modified lithium iron phosphate can be generated in situ under weak acid conditions, and dodecaphosphotungstic acid-modified lithium iron phosphate cannot be generated in situ under alkaline conditions.

[0157] 3) It can be seen from Example 1 and Comparative Example 2 that the positive electrode active material prepared by the molar ratio of lithium iron phosphate, sodium tungstate and disodium hydrogen phosphate provided in the examples of the present application has very high cycle stability.

[0158] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material comprises a lithium iron phosphate core modified with dodecaphosphotungstic acid; the core is followed by an ion conductor layer and a conductive carbon layer; The molar ratio of the lithium iron phosphate to the dodecaphosphotungstic acid is 12:0.01-0.

02.

2. The positive electrode active material according to claim 1, characterized in that The parameter range of the positive electrode active material satisfies at least one of the following (1) to (2): (1) The ion conductor layer is at least one layer, and the thickness of the single ion conductor layer is 2 nm to 30 nm; (2) The conductive carbon layer is at least one layer, and the thickness of the single conductive carbon layer is 5nm to 20nm.

3. The positive electrode active material according to claim 2, characterized in that The tap density of the positive electrode active material is 0.8 g / cm 3 ~1.35g / cm 3 .

4. A method for preparing a positive electrode active material, characterized in that: The steps include: The suspension is subjected to an acidification-hydrothermal reaction to obtain a lithium iron phosphate matrix modified with dodecaphosphotungstic acid; wherein the suspension comprises components of lithium iron phosphate, sodium tungstate and disodium hydrogen phosphate; The lithium iron phosphate matrix modified with dodecaphosphotungstic acid is dried and washed, and then spray granulated, ion conductor coated and carbon coated to obtain a positive electrode active material.

5. The method for preparing a positive electrode active material according to claim 4, characterized in that: The acidification-hydrothermal reaction comprises the steps of: Adjusting the pH value of the suspension to 6-7; The matrix is ​​obtained by performing a hydrothermal reaction at 120° C. to 135° C. for 10 h to 12 h.

6. The method for preparing a positive electrode active material according to claim 4 or 5, characterized in that: The molar ratio of the lithium iron phosphate, the sodium tungstate and the disodium hydrogen phosphate is 12:(0.12-0.2):(0.01-0.017).

7. The method for preparing a positive electrode active material according to claim 6, characterized in that: The spray drying includes pressure spray drying, in which the air inlet temperature is 200°C to 300°C, the air outlet temperature is 95°C to 100°C, and the air inlet pressure is 0.2MPa to 0.6MPa.

8. A positive electrode sheet, characterized in that: The positive electrode sheet includes the positive electrode active material according to any one of claims 1 to 3 or the positive electrode active material prepared by the preparation method according to any one of claims 4 to 7.

9. A battery comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte; characterized in that: The positive electrode sheet includes the positive electrode sheet according to claim 8.

10. Use of the positive electrode active material according to any one of claims 1 to 3, the positive electrode active material prepared by the method for preparing the positive electrode active material according to any one of claims 4 to 7, the positive electrode sheet according to claim 8 or the battery according to claim 9 in household appliances, electric vehicles, electric cars, electric trains, ships, satellites or energy storage systems.